A Study on Design, Development and Implementation of MOOCs by Faculty Members in Central Universities of India: Problems and Prospects - Purkayastha, Nilanjana; Sinha, Manoj Kumar (Journal of Information and Knowledge, 2023)
Technology is a promising development in education, allowing learning materials to be accessed anytime and anywhere, providing a global learning environment. MOOCs, Massive Open Online Courses, are designed to support unlimited participation of teacher/instructor and learner. Thousands of people can access knowledge disseminated across the globe through MOOCs, which can offer a solution to those who might have a problem limiting or compromising access to the traditional way of formal learning. Purpose: With the new education policy of having a virtual university, the creation of e-content and making them available on digital platforms, the Government of India has taken a step to modernize the education system of India. The creation of MOOCs platform Swayam is a very new initiative taken by the Government of India to promote online learning and offer quality education to people’s doorstep. UGC has urged all the universities to adopt online courses available on the Swayam platform and to motivate faculties to design and deliver MOOCs. The present study investigated the growth of MOOCs at the Swayam platform, and the involvement of Central University (CU) faculty in the design, development and implementation of MOOCs. Methodology: A census survey is conducted among the faculty of Central University, particularly those offering a MOOCs on the Swayam platform. The researchers used the Google Form platform to disseminate the questionnaires and collect responses. Findings: The findings of the study showed the existence of a total of 26 Central University faculty members offering MOOCs on the Swayam platform. Institutional Reputation, Creating National Identity and personal Interest are the factors motivating the design and delivery of MOOCs. The study also revealed the key factors required for designing MOOCs including support from the Institution, Hardware/Software Resources, Time for Designing MOOCs, Availability of Contents (OERs), Learning Contents for the Course, Instructor’s Role, Duration of the Course, Objectives of the Course and Pedagogical Approaches. Lack of Infrastructure is the most common problem faced by the faculty while designing MOOCs. Originality: The study is an original research work conducted using an online questionnaire, and the results drawn are based on the data received from the respondents.